Drug Development Targeting the Glycogen Synthase Kinase-3β (GSK-3β)-Mediated Signal Transduction Pathway: Role of GSK-3β in Myocardial Protection Against Ischemia/Reperfusion Injury - Tetsuji Miura; Masahiro Nishihara; Takayuki Miki (Elsevier, 2009)
Although reperfusion is required to salvage ischemic myocardium from necrosis, reperfusion per se induces myocardial necrosis. In this "lethal reperfusion injury", opening of the mitochondrial permeability transition pore (mPTP) upon reperfusion is crucially involved. The mPTP primarily consists of adenine nucleotide translocator (ANT) and voltage-dependent anion channel, and its opening is triggered by binding of cyclophilin-D (CyP-D) to ANT, which increases Ca2+ sensitivity of the mPTP. Recent studies have shown that inactivation of glycogen synthase kinase-3β (GSK-3β) suppresses mPTP opening and protects cardiomyocytes. Multiple intracellular signals relevant to cardiomyocyte protection converge to GSK-3β and inactivate this kinase by phosphorylation. Although the effect of GSK-3β phosphorylation on mPTP structure and function remains unclear, suppression of ANT-CyP-D interaction by binding of phospho-GSK-3β to ANT and reduction in GSK-3β-mediated phosphorylation of p53 may contribute to elevation of the threshold for mPTP opening. Furthermore, a significant inverse correlation was observed between level of phospho-GSK-3β at the time of reperfusion and the extent of myocardium infarction in heart. Together with the infarct size-limiting effect of GSK-3β inhibitors, this finding indicates that phospho-GSK-3β is a determinant of myocardial tolerance against reperfusion-induced necrosis. Thus, GSK-3β appears to be a target of novel therapy for cardioprotection upon reperfusion. Keywords:: glycogen synthase kinase-3β (GSK-3β), myocardial infarction, signal transduction, mitochondria, mitochondrial permeability transition pore